Aplikasi Joice (Jogja Choice) untuk Membantu Para Wisatawan Memilih Kafe Hits Berbasis Aplikasi Android - Octhavian, Harsel; Asriningtias, Yuli (Jurnal Locus Penelitian dan Pengabdian, 2025)
A significant number of tourist faced a problem in choosing a cafe that suits their preferences among the many options available in Yogyakarta. The JOICE (Jogja Choice) application is designed as an innovative solution to help travelers find hits and interesting cafes more easily. The application provides excellent features such as cafe recommendations based on reviews and location, specific search, transport route information, and full cafe details. The development of this application uses the System Development Life Cycle (SDLC) method with a waterfall approach, including the stages of planning, analysis, design, development, testing, implementation, and maintenance. The test results show that the JOICE application works well on Android devices and is able to provide a comfortable user experience. This application is expected to assist tourists in exploring cafes in Yogyakarta, while encouraging equal attention to cafes that are not yet widely known.